Influence of redox potential of the medium on phosphorus migration in sludge liquor - Юрченко, Валентина Александровна; Смирнов, Александр Владимирович; Бахарева, Анна Юрьевна (Eastern-European Journal of Enterprise Technologies, 2015)
The characteristics of the influence of the redox potential of the medium on the process of biological wastewater treatment from phosphates were investigated. The research was aimed at identifying new control actions to intensify wastewater treatment from phosphorus compounds and protect natural water bodies from pollution. The quantitative relationships were determined in the laboratory simulation of aerobic and anaerobic cultivation conditions of sludge liquor, as well as when examining existing sewage treatment facilities. It was found that the lower the redox potential values in the anaerobic wastewater treatment zones, the more intensive the phosphate mobilization from activated sludge into the aqueous medium and, consequently, the more phosphates will be immobilized from the aqueous medium into sludge under aerobic conditions. The obtained quantitative characteristics allow to use the redox potential of wastewater (controlled variable) to manage and intensify the deep removal of phosphorus compounds during biological wastewater treatment.